2018
DOI: 10.1186/s13104-018-3841-4
|View full text |Cite
|
Sign up to set email alerts
|

Healing rates in diabetes-related foot ulcers using low frequency ultrasonic debridement versus non-surgical sharps debridement: a randomised controlled trial

Abstract: ObjectiveCurrent clinical practice varies around debridement techniques used to promote healing of diabetes-related foot ulcers. This randomised controlled study will compare healing rates for diabetes-related foot ulcers treated with low frequency ultrasonic debridement versus non-surgical sharps debridement. Individuals with diabetes-related foot ulcers being managed by podiatry at a metropolitan hospital were screened against study criteria. Eligible participants were randomly allocated to either the non-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…In our study population, the time it took for ulcers to heal was significantly shorter in the UAW group than in the surgical group. In a RCT by Michailidis et al [ 32 ], they observed faster healing in DFU patients receiving non-surgical sharps debridement versus patients receiving UAW debridement. However, their results are unable to be generalized due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, the time it took for ulcers to heal was significantly shorter in the UAW group than in the surgical group. In a RCT by Michailidis et al [ 32 ], they observed faster healing in DFU patients receiving non-surgical sharps debridement versus patients receiving UAW debridement. However, their results are unable to be generalized due to the small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of this treatment modality has been assessed in a number of clinical trials, which generally concur that ultrasonic debridement is a valuable wound care adjuvant (Amini et al ., ; Murphy et al ., ). It is important to note that although these trials have demonstrated that ultrasonic debridement improves short‐term treatment outcomes, the frequency and total duration of the treatment are comparable to non‐surgical sharp debridement with no significant difference in healing rate between the modalities after 6 months of treatment (Amini et al ., ; Michailidis et al ., ).…”
Section: The Use Of Ultrasound Alone As An Anti‐biofilm Treatmentmentioning
confidence: 97%
“…New trends that have been subjects of interest recently include the negative-pressure wound therapy where tissues are healed in a given vacuum, getting rid of inflammations in the process [3]. Specialists of plastic surgery have also been involved in the treatment of pressure ulcers through the application of pedicled flaps [10]. Failure to treat pressure ulcers increase the risk of developing a malignant cancerlike ulcer called Marjolin's cancer [23].…”
Section: The Clinical Analysismentioning
confidence: 99%
“…Thirty patients had only one infected region, 11 had two areas, four patients had ulcers in three regions, and one male had decubitus in four regions [10]. It was also noted that some of the patients with multiple pressure ulcers received reconstructive surgeries at different stages as per the developing sores, which occurred at various times as well [11].…”
mentioning
confidence: 99%